Effect of Chitosan on Okra (Abelmoschus esculentus (L.) Moench) Seed Germination - Avinash B. Ade3, Sandhya Jaybhay1*, Asha Chate2 and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: medium none; padding-left: 0in; background: white; padding-bottom: 1pt; border-left: medium none; padding-top: 0in; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Present paper deals with the effect of chitosan at different concentration on seed germination of okra. It was revealed that chitosan at 0.03%, 0.12%,0.3% and 0.6% concentration induced seed germination in okra while at 0,03% there was maximum seed germination percentage as compare to other treatments. 1Department of Botany, Dr. Babasaheb Ambedkar Marathwada University, Aurangabad- 431 004 (MS), India; 2Department of Chemistry, Dr. Babasaheb Ambedkar Marathwada University, Aurangabad- 431 004 (MS), India; 3Department of Botany, University of Pune, Pune -411 007 (MS), India. * Corresponding Author, Email: jsandhya86@yahoo.in Please Cite This Article As: Sandhya Jaybhay, Asha Chate and Avinash B. Ade. 2010. Effect of Chitosan on Okra (Abelmoschus esculentus (L.) Moench) Seed Germination. J. Exp. Sci. 1(2): 27.